Prabowo’s Metaphor in International Stage: Case Study of Conceptual Metaphor Function in the Propositional Structure - Nisrina Dewi Ambarwati; Syihabbudin; Mahardhika Zifana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to identify and analyze the functions of conceptual metaphors used in Prabowo’s ASEAN summit’s speech, particularly in how they concretize abstract political challenges, personify values, and motivate collective actions. The data conducted in this study is taken from President Prabowo speech at ASEAN summit 2025. Beside classifying the conceptual metaphors, the mapping proposition structure by agent, actor, and object are also used in this study. By examining the domain source and target based on Lakoff and Johson theory of conceptual metaphor and also proposition by Lakoff and Johnson, the result shows that the most metaphorical expressions used in the speech is ontological metaphor. The findings highlight that the speech particularly demonstrates ontological metaphors to concretize abstract global political challenges while personifying values such as inclusivity, collaboration, and desire also create developmental, collaboration, and stability ideologies. Furthermore, the propositional mapping showed that the president as a leader or navigator collectively join in navigating and countering transboundary threats, thereby strengthening the persuasive function of the speech. Thus, this study provides an advance of the understanding of metaphors function in political communication and provides practical insights for improving rhetorical strategy and critical public discourse